Antibiotic prescribing pattern in paediatric in patients with first time wheezing - Pemde Harish K; Singh Varinder; Patra Soumya; Chandra Jagdish (BMC, 2011)
Abstract Background Acute wheezers for the first time in life are an important target group for efforts aimed at reducing unnecessary antibiotic use. Objective To evaluate the effect of clinical, laboratory and radiological data on the decision to prescribe antibiotics to paediatric patients with first time wheezing as well as to seek criteria that would justify antibiotic use. Methods A prospective study was made of 47 previous healthy children admitted to our hospital with first time wheezing in life between October 2008- March 2009. All the patients were treated as per the treating unit's protocol with oxygen, bronchodilators with or without antibiotics. The cases were analyzed after discharge and the characteristics of those treated with antibiotics (n = 23) were compared with those who were not (n = 24) and analyzed statistically to find the predictors for antibiotic usage. Results The mean age of the study groups was 5.8 (+/- 5.1) months. Among the clinical and investigational parameters, presence of predominant crackles and abnormalities on radiograph were the major determinants for antibiotic usage. There were no significant differences in final outcome between these groups. Conclusion Antibiotic usage in first time wheezers is still quite prevalent. Presence of crackles and radiological abnormalities often prompt the usage of antibiotics in such cases.